2019
DOI: 10.21203/rs.2.17477/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extended Spectrum Beta-Lactamase (ESBL) producing Escherichia coli and Klebsiella species in pediatric patients visiting International Friendship Children's Hospital, Kathmandu, Nepal

Abstract: Background Emergence of antibiotic resistance among pathogenic strains has spread due to production of β-lactamases, which can lead to failure of empirical therapy in clinical settings. Inappropriate use of antibiotics, particularly third generation cephalosporins has contributed to the development of antimicrobial resistance (AMR). This study aims to determine the prevalence of Extended Spectrum β-Lactamase (ESBL) production in E. coli and Klebsiella species isolated from various clinical samples. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 31 publications
8
12
0
Order By: Relevance
“…The increased and variable rate of colistin resistance may be due to quality, concentration and extensive use of colistin in the livestock farming [ 34 ]. In clinical samples, E. coli remains as the most frequently isolated organisms which is consistent with several previous studies from Nepal [ 35 38 ]. The higher load of E. coli in urine samples may be due to their main role in urinary tract infections [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased and variable rate of colistin resistance may be due to quality, concentration and extensive use of colistin in the livestock farming [ 34 ]. In clinical samples, E. coli remains as the most frequently isolated organisms which is consistent with several previous studies from Nepal [ 35 38 ]. The higher load of E. coli in urine samples may be due to their main role in urinary tract infections [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…In clinical samples, E. coli remains as the most frequently isolated organisms which is consistent with several previous studies from Nepal [ 35 38 ]. The higher load of E. coli in urine samples may be due to their main role in urinary tract infections [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…E. coli is a commensal of the mammalian gastrointestinal tract, but can also be found in water, soil, and vegetation [2]. Virtually all pathogenic strains of Gram-negative bacteria are responsible for several infections, including gastroenteritis, urinary tract infection (UTI), septicemia, nosocomial infections, pneumonia, brain and abdominal abscess, and neonatal meningitis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates of ESBLs have been reported from Southeast Asia, including Nepal [14]. Various studies have reported the circulation of ESBL-producing bacterial strains in Nepal [3,6,[15][16][17][18]. Laboratory facilities for culture and antimicrobial susceptibility testing in different peripheral/district hospitals are still not available in Nepal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation